The Effect of Health Education Using Audio Visual Simulation (SIMAV) Method on First Aid Knowledge of Adolescents in Kadugede Subdistrict, Kuningan Regency - Hendriana, Yana; Syarifudin Nur , Ayip (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
First aid knowledge among adolescents is crucial for handling emergency situations effectively. Health education using the Audio Visual Simulation (SIMAV) method is considered an interactive and efficient strategy to improve understanding. This study was conducted to assess the impact of SIMAV-based health education on adolescents’ knowledge of first aid in Kadugede Subdistrict, Kuningan Regency. A quasi-experimental design employing a one-group pretest–posttest approach without a control group was utilized. The study involved 17 adolescents who were selected using purposive sampling. Knowledge was measured using a validated questionnaire Data were collected prior to and following the intervention. The analysis was performed using the Wilcoxon Signed Ranks Test. The findings revealed that the average pre-test score was 58.24 (SD = 13.91), which increased to 80.29 (SD = 7.39) in the post-test. The Wilcoxon test demonstrated a statistically significant enhancement in participants’ knowledge after the intervention (p < 0.001).All participants demonstrated an increase in scores, with none showing a decrease or no change.Conclusion: Health education using the SIMAV method is effective in enhancing adolescents’ first aid knowledge and can be implemented as an interactive educational strategy.